Perlindungan Hak Kekayaan Intelektual Batik Tirta Suci dalam Perspektif Hukum Positif dan Hukum Islam - Sunaryo, Euis; Wasitaatmaja, Fokky Fuad; Machmud, Aris (Tasyri' : Journal of Islamic Law, 2025)
The Tirta Suci Kembang Mayang batik motif is a typical cultural expression of the city of Tangerang which was born from the creativity of the Kembang Mayang Batik Studio community. Although it has high philosophical and aesthetic value, this motif has not been officially registered in the Copyright system, even though its use has been widespread in various government activities. This study aims to analyze the legal protection of the batik motif both from the perspective of positive law and Islamic law. The method used is juridical-empirical legal research with a descriptive qualitative approach. Data was obtained through literature studies, interviews with batik artisans, and a review of Law Number 28 of 2014 concerning Copyright. The results of the study show that based on positive law, copyright to motif works arises automatically since they are realized in real form, but registration is still required as legal evidence. From the perspective of Islamic law, the appreciation of intellectual works is based on the principles of justice ('adl), the recognition of property rights (ḥaqq al-milkiyyah), and the prohibition of taking benefits without lawful permission (ghasab). Therefore, both in state law and Islamic law, the use of Tirta Suci batik motifs without moral recognition and economic compensation violates the principles of justice and the exclusive rights of the creator. This study recommends the integration of positive regulation with Islamic legal values as an ethical foundation in protecting local culture-based intellectual property.